The Utilization of Comic Media for Arabic Language Learning in Indonesia - Siti Nurhayati Solihah; Moch. Mu'izzuddin; Aspandi Aspandi; Siti Nurislamiah (Al-Muyassar: Journal of Arabic Education, 2025)
Arabic language learning in Indonesia faces various challenges, including low student interest and ineffective learning methods and tools used. One of the discoveries that can increase the effectiveness of learning is the use of comic media. Comics offer interesting visual and narrative elements, so they can increase interest in learning, facilitate understanding of the material, and develop language skills such as reading, writing, and expanding vocabulary. This study examines the effectiveness of comic media in Arabic language learning through a systematic literature review. The results of the analysis show that comics, both in print and digital formats, significantly increase students' learning motivation and help achieve better learning outcomes. Thus, comic media becomes a relevant and innovative learning alternative to be applied at various levels of education in Indonesia.Keywords: Comic Media, Arabic Language Learning, Utilization of Comic Media.